Oncoguides-ontoguides: protocols, panoramas and prehension in cancer treatment Oncoguías-ontoguías: protocolos, panoramas y prehensión en el tratamiento del cáncer - Francisco Javier Tirado Serrano; Jorge Castillo Sepúlveda (Athenea Digital, 2011)
The protocols and guides have been studied extensively by the social sciences, especially in the biomedical field. They have been characterized as sets of rules that require contextual adaptation, collecting heterogeneity of actors, times and spaces. In this article we collect two questions that, however, have not been treated in literature. The first rests on the organization of content of guides-protocols and their effects. The second, on the relationship established between them and the health professionals. Based on the analysis of medical protocols-guides developed for the diagnosis and treatment of cancer, we collect how these are organized in what Bruno Latour termed as panoramas. This implies a special relationship between professionals and guides-protocols, in which the seconds take the first, serving as a source of characterization of the medical phenomena. We describe this relationship as prehension, based on a neologism coined by Alfred Whitehead. Los protocolos y guías han sido estudiados ampliamente por las ciencias sociales, especialmente en el campo biomédico. Han sido caracterizados como conjuntos de normas que requieren de adaptación contextual, recogiendo heterogeneidad de actores, tiempos y espacios. En este artículo recogemos dos interrogantes que, sin embargo, no han sido tratadas en la literatura. La primera incumbe la organización del contenido de los protocolos-guías y sus efectos. La segunda, la relación que establecida entre estos y los profesionales de la salud. En base al análisis de protocolos-guías médicos elaborados para el diagnóstico y tratamiento del cáncer, recogemos cómo estos se organizan en lo que Bruno Latour denominó como panoramas. Ello supone una relación especial entre profesionales y protocolos-guía, en que los segundos prenden a los primeros, sirviendo de fuente de caracterización de los fenómenos médicos. Describimos esta relación como prehensión, en base a un neologismo acuñado por Alfred Whitehead.